DISTRIBUTED LEADERSHIP AND LEADERSHIP EFFECTIVENESS: AN ANALYTICAL STUDY OF SECONDARY SCHOOL PRINCIPALS AND TEACHERS IN MORADABAD DISTRICT - Chahal, Rupal; Arya, Mohan Lal (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Amid the changing paradigm of educational management, the mode of leadership practice has changed to the less hierarchical models to the more participatory model. This paper examines the influence of distributed leadership on leadership in secondary schools in the Moradabad district of Uttar Pradesh. The key purpose is to examine how collective leadership practices by principals and teachers can help to enhance institutional performance. Quantitative research design was followed, and the data were gathered with the help of the structured questionnaire that was provided to 150 respondents, such as principals and teachers of government and private schools. The research is based on descriptive statistics, correlation, and regression methods to test the correlation between the variables. The results indicate that there is a very strong positive correlation between distributed leadership and leadership effectiveness, which means that the schools where distributed leadership is practiced, shared decision making, delegation, and teacher involvement show a high level of performance and satisfaction. In addition, the research proposes teacher collaboration and effectiveness of communication as important mediating variables, which increases the contribution of distributed leadership. Comparison also shows differences in perceptions between principals and teachers, differences in schools of differing types, and the significance of institutional context is emphasized. The findings support the need to develop an interdisciplinary school culture and enhance leadership competency at various levels. The research has added to the small body of research on distributed leadership within Indian school setting and offers practical implications of the research to the educators and policymakers. It suggests that there should be distributed leadership practices incorporated in the school governance systems to promote the overall effectiveness and sustainability in education systems.